Solid electrolyte and preparation method and application thereof

Through the technical steps of wet ball milling and microwave heating sintering, the problems of long time, poor uniformity and low purity in the preparation of sulfide electrolytes are solved, and efficient and low-cost solid electrolyte preparation is achieved, and the circulation performance of all-solid-state batteries is improved.

CN119627193APending Publication Date: 2025-03-14ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1

Patent Information

Application Number
CN202411824655.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art has problems such as long preparation time, poor product uniformity, easy carbonization of organic impurities, low purity and high cost when preparing sulfide electrolytes, which seriously restricts the further development and application of sulfide electrolytes.

Method used

The technical steps of wet ball milling and microwave heating sintering include mixing the electrolyte raw materials evenly according to stoichiometric amounts, adding solvents to wet ball milling, and then vacuum drying and microwave heating sintering to obtain a solid electrolyte.

Benefits of technology

The preparation efficiency and purity of solid electrolytes are significantly improved, their uniformity and crystallinity are improved, the preparation cost is reduced, and the carbonization of organic impurities is inhibited, and the circulation performance of all solid state batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627193A_ABST
    Figure CN119627193A_ABST
Patent Text Reader

Abstract

The invention provides a solid electrolyte and a preparation method and application thereof, and the preparation method at least comprises the following steps: uniformly mixing a plurality of electrolyte raw materials according to stoichiometry to obtain a mixed raw material; adding a solvent into the mixed raw material, and carrying out wet ball milling to obtain an intermediate product; drying the intermediate product in vacuum to obtain an electrolyte precursor; and carrying out microwave heating sintering on the electrolyte precursor to obtain the solid electrolyte. According to the solid electrolyte and the preparation method and application thereof, the preparation efficiency, uniformity, crystallinity and purity of the solid electrolyte can be improved, carbonization of organic impurities is inhibited, the preparation cost is reduced, and the cycle performance of an all-solid-state battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a solid electrolyte and a preparation method and application thereof. Background Art

[0002] As a type of solid electrolyte, sulfide electrolyte has the advantages of high ionic conductivity, good interfacial compatibility with electrode materials and good electrochemical stability, which helps to improve the energy density and cycle life of all-solid-state batteries. However, the current methods for preparing sulfide electrolytes have problems such as long preparation time, poor product uniformity, easy carbonization of organic impurities, low purity and high cost, which seriously restrict the further development and application of sulfide electrolytes. Summary of the invention

[0003] The present invention proposes a solid electrolyte and a preparation method and application thereof. Through the solid electrolyte and the preparation method and application thereof provided by the present invention, the preparation efficiency, uniformity, crystallinity and purity of the solid electrolyte can be improved, the carbonization of organic impurities can be inhibited, the preparation cost can be reduced, and the cycle performance of the all-solid-state battery can be improved.

[0004] In order to solve the above technical problems, the present invention provides a method for preparing a solid electrolyte, which comprises at least the following steps:

[0005] Mixing multiple electrolyte raw materials evenly according to stoichiometric amounts to obtain a mixed raw material;

[0006] After adding a solvent to the mixed raw material, wet ball milling is performed to obtain an intermediate product;

[0007] vacuum drying the intermediate product to obtain an electrolyte precursor; and

[0008] The electrolyte precursor is subjected to microwave heating and sintering to obtain a solid electrolyte.

[0009] In one embodiment of the present invention, the mass ratio of the mixed raw material to the solvent is 1:(1-20).

[0010] In one embodiment of the present invention, the solvent is selected from at least one of toluene, chlorobenzene, xylene, anisole, dimethyl carbonate, N-methylformamide, n-heptane, n-decane, n-hexane, glycol dimethyl ether, dibutyl ether, ethanol, 1,2-ethylenediamine, 1,2-ethanedithiol, acetonitrile, tetrahydrofuran, methanol, isopropyl ether, acetone, hexene, ethyl acetate, benzyl acetate, butyl butyrate or diisobutyl ketone.

[0011] In one embodiment of the present invention, during the wet ball milling of the mixed raw materials, the ball-to-material mass ratio is 1:(1-30), the ball milling time is 0.1h-24h, and the ball milling speed is 1rpm-1000rpm.

[0012] In one embodiment of the present invention, during the vacuum drying of the intermediate product, the drying temperature is 25°C to 300°C, and the drying time is 0.1 h to 24 h.

[0013] In one embodiment of the present invention, during the microwave heating and sintering of the electrolyte precursor, the sintering temperature is 300°C to 600°C, and the sintering time is 0.1 h to 24 h.

[0014] The present invention also provides a solid electrolyte obtained by the above preparation method, and the chemical formula of the solid electrolyte is Li a P 1-b M b S c O d X e , wherein 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, and X is selected from at least one of Cl, Br or I.

[0015] The present invention also provides a solid electrolyte obtained by the above preparation method, and the chemical formula of the solid electrolyte is Li f P 1-g E g S w O g Q z , wherein 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, and Q is selected from at least one of Cl, Br or I.

[0016] The present invention also provides a all-solid-state battery, at least including:

[0017] a positive electrode plate;

[0018] a negative electrode plate; and

[0019] a solid electrolyte membrane disposed between the positive electrode plate and the negative electrode plate, and the solid electrolyte membrane includes the solid electrolyte obtained by the above preparation method, or the above solid electrolyte.

[0020] The present invention also provides an electronic device, including the above all-solid-state battery.

[0021] In summary, the present invention proposes a solid electrolyte and its preparation method and application. By combining wet ball milling and microwave heating sintering technology, the preparation efficiency of the solid electrolyte can be significantly improved, the preparation cost can be reduced, and the commercial application of the solid electrolyte can be facilitated. The uniformity and crystallinity of the solid electrolyte can be improved, and the ion conductivity of the solid electrolyte can be improved. The carbonization of organic impurities to form carbon impurities during the preparation process can be inhibited, and the purity of the solid electrolyte can be improved. The loss of sulfur in the solid electrolyte can be reduced, which helps to form an impurity phase. The cycle performance of the all-solid-state battery can be improved and the service life of the battery can be extended. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0023] Figure 1 This is a graph showing the results of a room temperature cycle performance test on the all-solid-state battery in Example 3 of the present invention. DETAILED DESCRIPTION

[0024] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0025] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0026] The technical scheme of the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] The present invention provides a method for preparing a solid electrolyte, which can be applied to the preparation process of various solid electrolytes. In the present invention, the chemical formula of the solid electrolyte is selected from Li a P 1-b M b S c Od X e or Li f P 1-g E g S w O g Q z Taking at least one of etc. as an example, the preparation method of the solid electrolyte will be described. Among them, in Li a P 1-b M b S c O d X e where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, etc., and X is selected from at least one of Cl, Br or I, etc. Further, M is, for example, selected from at least one of Sb, In or Bi, X is Cl, and the value range of b is, for example, 0 < b ≤ 0.1. More specifically, when M is, for example, a +5 valence element, b is, for example, 0.04, and when M is, for example, a +3 valence element, b is, for example, 0.02. By controlling the types of M and X elements in the solid electrolyte and the value range of b, the cycle performance of the battery can be improved, and thus the service life of the battery can be extended.

[0028] In one embodiment of the present invention, in Li f P 1-g E g S w O g Q z where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is, for example, selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, etc., and Q is, for example, selected from at least one of Cl, Br or I, etc. Further, E is, for example, Mg, Q is, for example, Cl, and the value range of g is, for example, 0.01 ≤ g ≤ 0.1. Specifically, g is, for example, 0.02. By controlling the types of E and Q elements in the solid electrolyte and the value range of g, the cycle performance of the battery can be improved, and thus the service life of the battery can be extended.

[0029] The preparation method of the solid electrolyte provided by the present invention includes at least steps S11 - S14.

[0030] Step S11: Mix a variety of electrolyte raw materials evenly according to stoichiometry to obtain a mixed raw material.

[0031] Step S12: After adding a solvent to the mixed raw material, perform wet ball milling to obtain an intermediate product.

[0032] Step S13: vacuum-dry the intermediate product to obtain an electrolyte precursor.

[0033] Step S14: Sintering the electrolyte precursor by microwave heating to obtain a solid electrolyte.

[0034] In one embodiment of the present invention, in step S11, first, in an atmosphere of an inert gas such as argon, according to the chemical formula of the solid electrolyte Li a P 1-b M b S c O d X e or Li f P 1-g E g S w O g Q z , a Li source, a P source, an M source, an S source and an X source, or a plurality of electrolyte raw materials such as a Li source, a P source, an E source, a S source and a Q source are mixed uniformly according to stoichiometric ratios to obtain a mixed raw material. Among them, the Li source is, for example, at least one selected from Li2S, LiCl, LiBr or LiI, the P source is, for example, P2S5, the M source is, for example, an oxide of M, the S source is, for example, from at least one of a Li source or a P source, the X source is, for example, from a Li source, the E source is, for example, an oxide of E, and the Q source is, for example, from a Li source.

[0035] In one embodiment of the present invention, after obtaining the mixed raw materials, in step S12, the mixed raw materials are placed in a ball mill, and a solvent is added to the mixed raw materials. The mixed raw materials and the solvent are wet-milled. Through high-energy impact and friction, the particles of the various electrolyte raw materials are refined, and chemical reactions are promoted between the electrolyte raw materials to obtain intermediate products. Wherein, the mass ratio of the mixed raw material and the solvent is, for example, 1: (1-20), the solvent is selected from at least one of toluene, chlorobenzene, xylene, anisole, dimethyl carbonate, N-methylformamide, n-heptane, n-decane, n-hexane, glycol dimethyl ether, dibutyl ether, ethanol, 1,2-ethylenediamine, 1,2-ethanedithiol, acetonitrile, tetrahydrofuran, methanol, isopropyl ether, acetone, hexene, ethyl acetate, benzyl acetate, butyl butyrate or diisobutyl ketone, etc., the ball material mass ratio of wet ball milling is, for example, 1: (1-30), the ball milling time is, for example, 0.1h-24h, and the ball milling speed is, for example, 1rpm-1000rpm. By replacing the high-temperature solid phase method and the mechanical ball milling method with wet ball milling, the particle size of the intermediate product and the solid electrolyte can be made uniform, thereby improving the ion conductivity of the solid electrolyte and improving the cycle performance of the battery. Moreover, by controlling the type of solvent, the ball milling speed and the ball milling time, the cycle performance of the battery can be further improved.

[0036] In one embodiment of the present invention, after obtaining the intermediate product, in step S13, the intermediate product is placed in a vacuum oven for example for drying to remove the solvent in the intermediate product to obtain an electrolyte precursor, wherein the drying temperature is, for example, 25° C. to 300° C., and the drying time is, for example, 0.1 h to 24 h.

[0037] In one embodiment of the present invention, after obtaining the electrolyte precursor, in step S14, the electrolyte precursor is placed in a graphite crucible, for example, and transferred to a microwave oven, and the electrolyte precursor is sintered by microwave heating, and the electrolyte precursor is annealed to obtain a solid electrolyte. Among them, the sintering temperature is, for example, 300°C to 600°C, and the sintering time is, for example, 0.1h to 24h. Ultra-fast targeted heating of the electrolyte precursor by microwave heating sintering can achieve rapid heating and high-temperature sintering, inhibit the carbonization reaction of organic impurities such as residual solvents or electrolyte precursors to generate carbon impurities, thereby improving the purity of the solid electrolyte, improving the electrochemical properties of the solid electrolyte and the cycle performance of the battery, and can also greatly shorten the sintering time, thereby improving the preparation efficiency of the solid electrolyte and reducing the preparation cost. Moreover, microwave heating sintering can reduce the loss of sulfur in the preparation process of the solid electrolyte, enhance the crystallinity of the solid electrolyte, and further improve the performance of the solid electrolyte and the cycle performance of the battery. Further, by controlling the sintering time, it is possible to improve the cycle performance of the battery while avoiding the problem of increased preparation costs caused by too long sintering time.

[0038] The present invention also provides an all-solid-state battery, for example, including a positive electrode plate, a negative electrode plate and a solid electrolyte membrane. Wherein, the solid electrolyte membrane is arranged between the positive electrode plate and the negative electrode plate, and the solid electrolyte membrane is obtained by cold pressing at a pressure of 300MPa to 400MPa by, for example, the above-mentioned solid electrolyte or the solid electrolyte obtained by the above-mentioned preparation method, and the thickness of the solid electrolyte membrane is, for example, 100μm to 500μm. In the present invention, the all-solid-state battery is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery or a cylindrical battery, etc. The present invention does not specifically limit the types and types of the all-solid-state battery.

[0039] In one embodiment of the present invention, the positive electrode plate includes, for example, a positive electrode active layer, and the positive electrode active layer includes, for example, a positive electrode active material, a positive electrode electrolyte, a conductive agent, and a binder. Among them, the present invention does not limit the mass ratio of the positive electrode active material, the positive electrode electrolyte, the conductive agent, and the binder, which can be selected according to actual needs. In other embodiments of the present invention, in addition to the positive electrode active layer, the positive electrode plate may also include a positive electrode collector, and the positive electrode collector is coated with a positive electrode active layer on the surface of at least one side. Among them, the positive electrode collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric.

[0040] In one embodiment of the present invention, in the positive electrode active layer, the positive electrode active material is selected from at least one of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO) or lithium nickel cobalt aluminum oxide (NCA), the positive electrode electrolyte is a halide solid electrolyte, the conductive agent is selected from at least one of graphite, graphene, conductive carbon black (SuperP), nanocarbon fiber (vapor-grown carbon fiber, VGCF) or carbon nanotubes, and the binder is selected from polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinyl pyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAN), etc. At least one of polyol, polyurethane, polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer, styrene-butadiene rubber, fluorine rubber, β-cyclodextrin polymer (β-cyclodextrin, β-CDp), polypropylene emulsion (LA132), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene-propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride-hexafluoropropylene copolymer or vinylidene fluoride-chlorotrifluoroethylene copolymer.

[0041] In one embodiment of the present invention, the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O2, the positive electrode electrolyte is for example Li 2.35 Zr0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The conductive agent includes, for example, SuperP and VGCF, and the mass ratio of SuperP to VGCF is, for example, 1:1, and the binder is, for example, PTFE. After the positive electrode active material, the positive electrode electrolyte, the conductive agent and the binder are uniformly mixed in a mass ratio of, for example, 69:29:1:1, the positive electrode sheet is directly obtained by dry pressing.

[0042] In another embodiment of the present invention, the positive electrode current collector is, for example, aluminum foil, and the positive electrode active material is, for example, LiNi 0.8 Co 0.1 Mn 0.1 O2, the positive electrode electrolyte is for example Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The conductive agent includes, for example, SuperP and VGCF, and the mass ratio of SuperP to VGCF is, for example, 1:1, and the binder is, for example, PTFE. The positive electrode active material, the positive electrode electrolyte, the conductive agent and the binder are mixed evenly in a mass ratio of, for example, 69:29:1:1, and then rolled and covered on the surface of the aluminum foil to obtain a positive electrode sheet.

[0043] In one embodiment of the present invention, the negative electrode plate is selected from at least one of a metal lithium plate, a metal indium plate or a lithium indium alloy plate. In other embodiments of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active layer coated on at least one surface of the negative electrode current collector. Among them, the negative electrode current collector is, for example, a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector or a stainless steel current collector, and the negative electrode active layer includes, for example, a negative electrode active material, a negative electrode electrolyte, a conductive agent and a binder. The present invention does not limit the mass ratio of the negative electrode active material, the negative electrode electrolyte, the conductive agent and the binder, and can be selected according to actual needs.

[0044] In one embodiment of the present invention, the negative electrode active material is selected from at least one of graphite materials or silicon materials, the negative electrode electrolyte is, for example, a sulfide solid electrolyte, the conductive agent is selected from at least one of graphite, graphene, SuperP, VGCF or carbon nanotubes, and the adhesive is selected from at least one of PVDF, CMC, SBR, PVP, PMMA, PAN, PAA, polyurethane, PVA, Alg, ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, β-CDp, LA132, PTFE, ETFE, FEP, PFA, PCTFE, ECTFE, polyvinylidene fluoride-hexafluoropropylene copolymer or vinylidene fluoride-chlorotrifluoroethylene copolymer.

[0045] In one embodiment of the present invention, the negative electrode current collector is, for example, a copper foil current collector, the negative electrode active material is, for example, silicon, the negative electrode electrolyte is, for example, a sulfide solid electrolyte, the conductive agent is, for example, SuperP, and the binder is, for example, PTFE. The negative electrode active material, the negative electrode electrolyte, the conductive agent, and the binder are mixed evenly in a mass ratio of, for example, 72:20:5:3, and then rolled and covered on the surface of the copper foil current collector to obtain a negative electrode sheet.

[0046] In one embodiment of the present invention, the above-mentioned positive electrode sheet, solid electrolyte membrane and negative electrode sheet are sequentially stacked, packaged, hot pressed and cold pressed to assemble into an all-solid-state battery. The assembly process of the all-solid-state battery is completed in an inert atmosphere glove box.

[0047] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0048] Example 1

[0049] Preparation of solid electrolyte: Under argon atmosphere, 2 mol of Li2S, 1.5 mol of LiCl, 0.48 mol of P2S5 and 0.02 mol of Sb2O5 were mixed evenly to obtain a mixed raw material, and the mixed raw material and acetonitrile solvent were added to a ball mill for wet ball milling to obtain an intermediate product, wherein the mass ratio of the mixed raw material to the acetonitrile solvent was 1:10, the ball-to-material ratio was 20:1, the rotation speed was 100 rpm, and the ball milling time was 1 hour. After the ball milling, the intermediate product was dried in a vacuum oven at 80°C for 12 hours to obtain an electrolyte precursor, and the electrolyte precursor was placed in a graphite crucible and transferred to a microwave oven, and microwaved and sintered at 500°C for 2 hours to obtain Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 Solid electrolyte.

[0050] Preparation of solid electrolyte membrane: The solid electrolyte prepared above was cold pressed at 350 MPa to obtain a 300 μm solid electrolyte membrane.

[0051] Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 O2 positive electrode active material, Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5The positive electrode electrolyte, the conductive agent and PTFE are mixed evenly in a mass ratio of 69:29:1:1, for example, and then the positive electrode sheet is obtained by dry pressing and cut into discs with a diameter of 10 mm. The conductive agent includes SuperP and VGCF, and the mass ratio of SuperP to VGCF is, for example, 1:1.

[0052] Choice of negative electrode: Choose metallic lithium as the negative electrode.

[0053] Battery preparation: The positive electrode sheet, solid electrolyte membrane and negative electrode sheet are stacked, packaged, hot pressed and cold pressed in sequence to assemble into an all-solid-state battery.

[0054] Example 2

[0055] The difference between this embodiment and embodiment 1 is that the solvent is xylene.

[0056] Example 3

[0057] The difference between this embodiment and embodiment 1 is that the solvent is butyl butyrate.

[0058] Example 4

[0059] The difference between this embodiment and embodiment 1 is that the solvent is benzyl acetate.

[0060] Example 5

[0061] The difference between this embodiment and embodiment 3 is that the rotation speed during the wet ball milling process is 1 rpm.

[0062] Example 6

[0063] The difference between this embodiment and embodiment 3 is that the rotation speed during the wet ball milling process is 50 rpm.

[0064] Example 7

[0065] The difference between this embodiment and embodiment 3 is that the rotation speed during the wet ball milling process is 500 rpm.

[0066] Example 8

[0067] The difference between this embodiment and embodiment 3 is that the rotation speed during the wet ball milling process is 1000 rpm.

[0068] Example 9

[0069] The difference between this embodiment and embodiment 3 is that the wet ball milling time is 0.1 h.

[0070] Example 10

[0071] The difference between this embodiment and embodiment 3 is that the wet ball milling time is 0.5 h.

[0072] Embodiment 11

[0073] The difference between this embodiment and embodiment 3 is that the wet ball milling time is 5 hours.

[0074] Example 12

[0075] The difference between this embodiment and embodiment 3 is that the wet ball milling time is 10 hours.

[0076] Example 13

[0077] The difference between this embodiment and embodiment 3 is that the wet ball milling time is 24 hours.

[0078] Embodiment 14

[0079] The difference between this embodiment and embodiment 3 is that the microwave heating sintering time is 0.1 h.

[0080] Embodiment 15

[0081] The difference between this embodiment and embodiment 3 is that the microwave heating sintering time is 0.5h.

[0082] Example 16

[0083] The difference between this embodiment and embodiment 3 is that the microwave heating sintering time is 1 hour.

[0084] Embodiment 17

[0085] The difference between this embodiment and embodiment 3 is that the microwave heating sintering time is 10 hours.

[0086] Embodiment 18

[0087] The difference between this embodiment and embodiment 3 is that the microwave heating sintering time is 24 hours.

[0088] Embodiment 19

[0089] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.99 Sb 0.0 1S 4.475 O 0.025 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.05 mol of Sb2O5.

[0090] Embodiment 20

[0091] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.94 Sb 0.06 S 4.35 O 0.15 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of Sb2O5.

[0092] Embodiment 21

[0093] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.9 Sb 0.1 S 4.25 O 0.25 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of Sb2O5.

[0094] Embodiment 22

[0095] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 P 0.96 Sb 0.0 4S 4.40 O 0.10 Cl 1.3 Br 0.1 I 0.1 The raw materials are 2 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI, 0.48 mol of P2S5 and 0.02 mol of Sb2O5.

[0096] Embodiment 23

[0097] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.52 P 0.99 In 0.0 1S 4.485 O 0.015 Cl 1.5 The raw materials are 2.01 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.005 mol of In2O3.

[0098] Embodiment 24

[0099] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li5.54 P 0.98 In 0.0 2S 4.47 O 0.03 Cl 1.5 The raw materials are 2.02 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.01 mol of In2O3.

[0100] Embodiment 25

[0101] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.62 P 0.94 In 0.0 6S 4.41 O 0.09 Cl 1.5 The raw materials are 2.06 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of In2O3.

[0102] Embodiment 26

[0103] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.7 P 0.9 In 0.1 S 4.35 O 0.15 Cl 1.5 The raw materials are 2.1 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of In2O3.

[0104] Embodiment 27

[0105] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 In 0.0 2S 4.47 O 0.03 Cl 1.3 Br 0.1 I 0.1 The raw materials are 2.02 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI, 0.49 mol of P2S5 and 0.01 mol of In2O3.

[0106] Embodiment 28

[0107] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.52 P 0.99 Bi0.0 1S 4.485 O 0.015 Cl 1.5 The raw materials are 2.01 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.005 mol of Bi2O3.

[0108] Embodiment 29

[0109] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 Bi 0.0 2S 4.47 O 0.03 Cl 1.5 The raw materials are 2.02 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.01 mol of Bi2O3.

[0110] Embodiment 30

[0111] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.62 P 0.94 Bi 0.0 6S 4.41 O 0.09 Cl 1.5 The raw materials are 2.06 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of Bi2O3.

[0112] Embodiment 31

[0113] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.7 P 0.9 Bi 0.1 S 4.35 O 0.15 Cl 1.5 The raw materials are 2.1 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of Bi2O3.

[0114] Embodiment 32

[0115] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.54 P 0.98 Bi 0.0 2S 4.47 O 0.03 Cl 1.3 Br 0.1 I 0.1The raw materials are 2.02 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI, 0.49 mol of P2S5 and 0.01 mol of Bi2O3.

[0116] Embodiment 33

[0117] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.53 P 0.99 Mg 0.0 1S 4.49 O 0.01 Cl 1.5 The raw materials are 2.015 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.01 mol of MgO.

[0118] Embodiment 34

[0119] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.56 P 0.98 Mg 0.0 2S 4.48 O 0.02 Cl 1.5 The raw materials are 2.03 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.02 mol of MgO.

[0120] Embodiment 35

[0121] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.68 P 0.94 Mg 0.0 6S 4.44 O 0.06 Cl 1.5 The raw materials are 2.09 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.06 mol of MgO.

[0122] Embodiment 36

[0123] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.8 P 0.9 Mg 0.1 S 4.48 O 0.1 Cl 1.5 The raw materials are 2.15 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.1 mol of MgO.

[0124] Embodiment 37

[0125] The difference between this embodiment and embodiment 3 is that the chemical formula of the sulfide electrolyte is Li 5.56 P 0.98 Mg 0.0 2S 4.48 O 0.02 Cl 1.3 Br 0.1 I 0.1 The raw materials are 2.03 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI, 0.49 mol of P2S5 and 0.02 mol of MgO.

[0126] Comparative Example 1

[0127] The difference between this comparative example and Example 3 is that the chemical formula of the sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The raw materials are 2 mol of Li2S, 1.5 mol of LiCl and 0.5 mol of P2S5.

[0128] Comparative Example 2

[0129] The difference between this comparative example and Example 3 is: the preparation process of the intermediate product. Specifically, in this comparative example, the mixed raw material and the butyl butyrate solvent were stirred on a magnetic stirrer at a rotation speed of 100 rpm for 1 hour to obtain an intermediate product, wherein the mass ratio of the mixed raw material to the butyl butyrate solvent was 1:10.

[0130] Comparative Example 3

[0131] The difference between this comparative example and Example 3 is that after obtaining the electrolyte precursor, it is placed in a graphite crucible, transferred to a muffle furnace, and sintered at 500°C for 2h to obtain Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 Solid electrolyte sulfide electrolyte.

[0132] The parameters of the preparation process of the solid electrolyte in each embodiment and comparative example are shown in Table 1.

[0133] Table 1. Parameters of solid electrolytes in Examples 1 to 37 and Comparative Examples 1 to 3

[0134]

[0135]

[0136]

[0137] In the present invention, performance tests were performed on all-solid-state batteries prepared using different solid electrolyte membranes in Examples 1 to 37 and Comparative Examples 1 to 3.

[0138] See also Figure 1 As shown, in one embodiment of the present invention, for example, the all-solid-state battery in Example 3 is subjected to a room temperature cycle performance test. Specifically, at 25°C, the all-solid-state battery is cycled at a charge and discharge rate of 1C / 1C in a specified voltage range of 2.5V-4.3V to obtain the capacity (CC) and coulombic efficiency (CE) at different cycle numbers. Figure 1 It can be seen that with the increase in the number of cycles, the attenuation trend of the battery CC is relatively gentle, and the battery CE does not fluctuate and stabilizes at around 100%, which indicates that the battery has good cycle performance.

[0139] Please refer to Table 2. In one embodiment of the present invention, for example, the all-solid-state batteries in Examples 1 to 37 and Comparative Examples 1 to 3 are subjected to a room temperature cycle stability test. Specifically, at 25°C, the all-solid-state battery is cycled at a charge and discharge rate of 1C / 1C in a specified voltage range of 2.5V-4.3V. The test is terminated when the battery capacity reaches 80% of the first cycle capacity State of Health (SOH), and the number of room temperature cycles of the battery is recorded. The recorded results are shown in Table 2.

[0140] Table 2. Test results of all-solid-state batteries in Examples 1 to 37 and Comparative Examples 1 to 3

[0141] Group Normal temperature cycle number (80% SOH) Example 1 423 Example 2 512 Example 3 567 Example 4 489 Example 5 223 Example 6 416 Example 7 523 Example 8 442 Example 9 327 Example 10 405 Embodiment 11 538 Example 12 473 Example 13 412 Embodiment 14 345 Embodiment 15 439 Example 16 527 Embodiment 17 568 Embodiment 18 570 Embodiment 19 117 (short circuit) Embodiment 20 524 Embodiment 21 399 Embodiment 22 485 Embodiment 23 116 (short circuit) Embodiment 24 542 Embodiment 25 446 Embodiment 26 404 Embodiment 27 442 Embodiment 28 99(short circuit) Embodiment 29 524 Embodiment 30 428 Embodiment 31 396 Embodiment 32 424 Embodiment 33 103 (short circuit) Embodiment 34 508 Embodiment 35 412 Embodiment 36 325 Embodiment 37 408 Comparative Example 1 1(Short circuit) Comparative Example 2 87 Comparative Example 3 93

[0142] As shown in Table 1 and Table 2, it can be seen from Comparative Examples 1-4 that among the four solvents of acetonitrile, xylene, butyl butyrate and benzyl acetate, the battery obtained by using butyl butyrate solvent has the largest number of normal temperature cycles, that is, the battery has the best cycle performance, which shows that: in the process of synthesizing the intermediate product, the type of solvent affects the performance of the solid electrolyte, thereby affecting the cycle performance of the battery. Therefore, by changing the type of solvent, the cycle performance of the battery can be improved.

[0143] Please refer to Table 1 and Table 2. Comparison of Examples 3, 5 to 8 shows that during the synthesis of the intermediate product, as the rotation speed increases, the number of normal temperature cycles of the battery first increases gradually, and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing, which indicates that: when the rotation speed is too low, the particle size of the intermediate product and the solid electrolyte may be uneven, and the lattice defects may increase, thereby affecting the ion transmission efficiency and causing the battery to have poor cycle performance. When the rotation speed is too high, the structure of the intermediate product and the solid electrolyte may be excessively damaged, causing the performance of the solid electrolyte to decrease, thereby also causing the battery to have poor cycle performance. Therefore, by controlling the rotation speed during the synthesis of the intermediate product, the performance of the solid electrolyte can be improved, thereby improving the cycle performance of the battery.

[0144] Please refer to Table 1 and Table 2. Comparison of Examples 3, 9 to 13 shows that in the synthesis process of the intermediate product, as the synthesis time is extended, the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing, which indicates that: when the synthesis time is too short, the particle size of the intermediate product and the solid electrolyte may be uneven, and the lattice defects may increase, thereby affecting the ion transmission efficiency and causing the battery to have poor cycle performance. When the synthesis time is too long, the electrolyte raw materials and the solvent may over-react, causing the performance of the solid electrolyte to decrease, thereby also causing the battery to have poor cycle performance. Therefore, by controlling the time of the intermediate product synthesis process, the performance of the solid electrolyte can be improved, thereby improving the cycle performance of the battery.

[0145] Please refer to Table 1 and Table 2. By comparing Examples 3, 14 to 18, it can be seen that in the process of heating and sintering the electrolyte precursor, as the heating and sintering time increases, the number of normal temperature cycles of the battery first gradually increases and then tends to stabilize, that is, the cycle performance of the battery shows a trend of first improving and then tending to stabilize, which shows that: when the heating and sintering time is too short, it may cause incomplete crystal formation of the solid electrolyte, causing the performance of the solid electrolyte to decrease, thereby resulting in poor battery cycle performance. When the heating and sintering time is too long, the effect of improving the battery cycle performance is not significant, and the cost will also increase. Therefore, by controlling the time of heating and sintering the electrolyte precursor, the preparation cost can be reduced while improving the battery cycle performance.

[0146] Please refer to Table 1 and Table 2. Comparison of Examples 3, 19 to 21 shows that with the increase in the doping amount of the Sb element in the solid electrolyte, the number of normal temperature cycles of the battery first increases gradually, and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Please refer to Table 1 and Table 2. Comparison of Examples 23 to 26 shows that with the increase in the doping amount of the In element in the solid electrolyte, the number of normal temperature cycles of the battery first increases gradually, and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Please refer to Table 1 and Table 2. Comparison of Examples 28 to 31 shows that with the increase in the doping amount of the Bi element in the solid electrolyte, the number of normal temperature cycles of the battery first increases gradually, and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the doping amount of the M element in the solid electrolyte, the cycle performance of the battery can be improved.

[0147] As shown in Table 1 and Table 2, by comparing Examples 33 to 36, it can be seen that as the doping amount of the Mg element in the solid electrolyte increases, the number of normal temperature cycles of the battery first gradually increases and then gradually decreases, that is, the cycle performance of the battery shows a trend of first increasing and then decreasing. Therefore, by controlling the doping amount of the E element in the solid electrolyte, the cycle performance of the battery can be improved.

[0148] Refer to Table 1 and Table 2, and compare Example 3 with Example 22, Example 24 with Example 27, Example 29 with Example 32, and Example 34 with Example 37. When the doping amount of Sb, In, Bi or Mg in the solid electrolyte is the same, if Br and I are doped into the solid electrolyte, the number of normal temperature cycles of the battery will also decrease, that is, the cycle performance of the battery will decrease. Therefore, by controlling the number of element types contained in X or Q in the solid electrolyte, the cycle performance of the battery can be further improved.

[0149] Please refer to Table 1 and Table 2. By comparing Example 3, Example 24, Example 29, Example 34 and Comparative Example 1, it can be seen that when the solid electrolyte is not doped with Sb, Bi, In or Mg elements, the number of normal temperature cycles of the battery is only 1, and the battery short-circuit occurs, which shows that the Sb, Bi, In or Mg elements doped in the solid electrolyte can significantly improve the cycle performance of the battery. Therefore, by controlling the type of M or E elements in the solid electrolyte, the cycle performance of the battery can be improved.

[0150] Please refer to Table 1 and Table 2. By comparing Example 3 and Comparative Example 2, it can be seen that when the intermediate product is synthesized by magnetic stirring, the number of normal temperature cycles of the battery is only 87, and there is almost no cycle performance. When the intermediate product is synthesized by wet ball milling, the number of normal temperature cycles of the battery is significantly improved, that is, the cycle performance of the battery is significantly improved, which shows that wet ball milling can quickly prepare a solid electrolyte with good uniformity, thereby improving the ion conductivity of the solid electrolyte, and then improving the cycle performance of the battery. Therefore, by controlling the synthesis method of the intermediate product, the performance of the solid electrolyte can be improved, and then the cycle performance of the battery can be improved.

[0151] Please refer to Table 1 and Table 2. It can be seen from Example 3 and Comparative Example 3 that when the electrolyte precursor is sintered in a muffle furnace, the number of normal temperature cycles of the battery is only 93, and when the electrolyte precursor is sintered by microwave heating, the number of normal temperature cycles of the battery is significantly improved, that is, the cycle performance of the battery is significantly improved, which shows that microwave sintering performs ultra-fast targeted heating of the electrolyte precursor to achieve rapid heating and high-temperature sintering. On the one hand, it can inhibit the carbonization reaction of residual solvents or electrolyte precursors to generate carbon impurities, thereby improving the purity of the solid electrolyte, improving the electrochemical properties of the solid electrolyte and the cycle performance of the battery. On the other hand, it can reduce the sulfur loss in the preparation process of the solid electrolyte and enhance the crystallinity of the solid electrolyte, thereby further improving the performance of the solid electrolyte and the cycle performance of the battery. Therefore, by controlling the synthesis method of the intermediate product, the performance of the solid electrolyte can be improved, and then the cycle performance of the battery can be improved.

[0152] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned all-solid-state batteries, and the all-solid-state battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned all-solid-state battery, and therefore includes the advantages of the above-mentioned all-solid-state battery, which will not be elaborated here.

[0153] In summary, the present invention proposes a solid electrolyte and its preparation method and application. Through wet ball milling, the uniformity of the solid electrolyte can be improved and the ion conductivity of the solid electrolyte can be improved. Through microwave heating and sintering, on the one hand, the preparation efficiency of the solid electrolyte can be significantly improved, the preparation cost can be reduced, and the commercial application of the solid electrolyte can be facilitated. On the other hand, the carbonization of organic impurities in the preparation process can be inhibited to generate carbon impurities, the purity and crystallinity of the solid electrolyte can be improved, and the loss of sulfur in the solid electrolyte can be reduced, which is conducive to the formation of impurity phases, thereby improving the cycle performance of the all-solid-state battery and extending the service life of the battery.

[0154] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0155] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A method for preparing a solid electrolyte, characterized in that: At least the following steps are included: Mixing multiple electrolyte raw materials evenly according to stoichiometric amounts to obtain a mixed raw material; After adding a solvent to the mixed raw material, wet ball milling is performed to obtain an intermediate product; vacuum drying the intermediate product to obtain an electrolyte precursor; and The electrolyte precursor is subjected to microwave heating and sintering to obtain a solid electrolyte.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the mixed raw material to the solvent is 1:(1-20).

3. The preparation method according to claim 1, characterized in that: The solvent is selected from at least one of toluene, chlorobenzene, xylene, anisole, dimethyl carbonate, N-methylformamide, n-heptane, n-decane, n-hexane, glycol dimethyl ether, dibutyl ether, ethanol, 1,2-ethylenediamine, 1,2-ethanedithiol, acetonitrile, tetrahydrofuran, methanol, isopropyl ether, acetone, hexene, ethyl acetate, benzyl acetate, butyl butyrate or diisobutyl ketone.

4. The preparation method according to claim 1, characterized in that: During the wet ball milling of the mixed raw materials, the ball-to-material mass ratio is 1:(1-30), the ball milling time is 0.1h-24h, and the ball milling speed is 1rpm-1000rpm.

5. The preparation method according to claim 1, characterized in that: During the vacuum drying of the intermediate product, the drying temperature is 25° C. to 300° C., and the drying time is 0.1 h to 24 h.

6. The preparation method according to claim 1, characterized in that: During the microwave heating sintering of the electrolyte precursor, the sintering temperature is 300° C. to 600° C., and the sintering time is 0.1 h to 24 h.

7. A solid electrolyte obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The chemical formula of the solid electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M is selected from at least one of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, and X is selected from at least one of Cl, Br or I.

8. A solid electrolyte obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The chemical formula of the solid electrolyte is Li f P 1-g E g S w O g Q z , where 5 < f < 10, 0 < g < 1, 3 < w < 6, 4 < w + g < 6, 0 < z < 2, E is selected from at least one of Mg, Ca, Sr, Ba, Zn, Cr, Sn or Pb, and Q is selected from at least one of Cl, Br or I.

9. An all-solid-state battery, characterized in that: At least: Positive electrode; Negative electrode; as well as A solid electrolyte membrane is arranged between the positive electrode plate and the negative electrode plate, and the solid electrolyte membrane comprises a solid electrolyte obtained by the preparation method described in any one of claims 1 to 6, or a solid electrolyte described in any one of claims 7 to 8.

10. An electronic device, characterized in that: Including the all-solid-state battery as described in claim 9.

Citation Information

Patent Citations

  • Method for preparing beta-SiC by using microwave sintering

    CN107128924A

  • Method for preparing crystalline sulfide solid electrolyte material containing halogen group elements at large scale

    CN110718713A

  • Preparation method of sulfide solid electrolyte

    CN111908437A

  • Solid electrolyte and method for producing same

    CN114207898A

  • Lithium-rich high temperature resistant sulfide electrolyte

    CN115911519A

Cited By

  • Doping modified sulfide electrolyte and preparation method thereof

    CN120657236A